Manajemen Komunikasi BBKBN Dalam Pencegahan Seks Bebas: Studi Kasus Program GenRe di BKKBN Jawa Timur - Rahma Ayumi Saidah; Anam Miftakhul Huda (The Commercium, 2025)
Free sex is still a serious problem in Indonesia, especially among teenagers, and is often associated with criminalization of sex outside of marriage. Factors such as social environment, communication in relationships, and technological developments that facilitate access to information have contributed to the increase in this behavior. To overcome this problem, the Population and Family Planning Agency (BKKBN) through the Generation Planning (GenRe) program seeks to provide education to teenagers aged 10-24 years so that they can protect themselves and avoid free sex. This study aims to examine the communication strategies used by the East Java BKKBN in socializing the GenRe program in the province. Using a descriptive qualitative method with a case study approach, this study collected data through participant observation and interviews to understand the communication model applied. The results showed that the East Java BKKBN conveyed educational messages about the importance of adolescent reproductive health and future planning through verbal and non-verbal media, both directly and virtually, in order to form independent, healthy teenagers who are free from reproductive health problems.